Characterization of antigen-presenting activity of intestinal mononuclear cells isolated from normal and inflammatory bowel disease colon and ileum. - Mahida, Y; Wu, K; Jewell, D (1988)
Antigen-presenting activity in mononuclear cells, isolated from normal and inflamed human ileum and colon, has been characterized using allogeneic mixed lymphocyte reaction with resting T cells as responders. Greatest proliferation was induced by fibronectin-adherent (macrophage-enriched) cells, and least by fibronectin non-adherent (macrophage-depleted) cells and by mononuclear cells depleted of macrophages by panning with monoclonal antibody 3C10. When intestinal mononuclear cells and allogeneic T cells were incubated in large numbers, clusters were observed. These clusters contained cells with a dendritic morphology that were strongly HLA-D-positive and which also stained with macrophage-specific monoclonal antibodies 3C10, EMB11 and Y1/82A. These cells were closely associated with proliferating T cells. Studies comparing mononuclear cells isolated from normal and inflamed colonic mucosa suggest that the latter may have enhanced antigen-presenting capacity.